Case Report: Distinctive features of cognitive dysfunction and amelioration by antiseizure medication in neuronal intranuclear inclusion disease - Ohara, Hiroya; Yamanaka, Masami; Okada, Fumi; Okazaki, Aiko; Dizon, Marisse Dy; Elangovan, Ajay; Babu, Harysh Winster Suresh; Iyer, Mahalaxmi; Vellingiri, Balachandar; Kinoshita, Masako (Frontiers in Neuroscience, 2026)
AimNeuronal intranuclear inclusion disease (NIID) is a rare neurodegenerative disease. We investigated a role of nonconvulsive status epilepticus (NCSE) in cognitive dysfunction in pathologically confirmed NIID. We also analyzed distinctive factors to differentiate NIID from Alzheimer’s disease (AD).MethodsA 63-year-old man presented with transient consciousness disturbance (Day 1). For previous 6 years he had been suffering from similar episodes and gradually progressive cognitive decline. Clinical characteristics and response to antiseizure medications (ASM) were analyzed with a narrative literature review.ResultsNeurological examination showed disorientation, memory disturbance, aphasia, agraphia, and impaired visuospatial ability. On Day 27, his MMSE scored 10. Diffusion-weighted MRI showed high intensity signal in the corticomedullary junction of the frontal lobe, which could not explain his neurological manifestations. EEG showed seizure patterns arising from the bilateral occipital areas. ASM improved MMSE score to 23. Skin biopsy confirmed his diagnosis as dementia-dominant sporadic NIID. He died on Day 77. Cognitive dysfunction in visuospatial execution, manifested by impaired pentagon drawing and agraphia of both kanji (Japanese morphograms) and kana (Japanese syllabograms), its fluctuating course, and reactivity to ASM were clear distinction from AD.ConclusionNCSE can accelerate cognitive decline and ASM can improve cognitive function in NIID. Cognitive evaluation using pentagon drawing and handwriting of both morphograms and syllabograms can be useful to differentiate NIID from AD.